FAMILY COMMUNICATION PATTERNS IN OVERCOMING THE NEGATIVE IMPACT OF THE INTERNET IN ONLINE LEARNING PERIOD DURING THE COVID-19 PANDEMIC IN MEDAN CITY - Kartika Ayu Br Ginting; Ribut Priadi (Journal of Islamic, Social, Economics and Development, 2023)
Online learning causes teenagers to stay connected to the internet longer. This condition is believed to have a negative impact on children. The purpose of this study was to analyze Family Communication Patterns in Overcoming the Negative Impacts of the Internet in the Online Study Period During the Covid 19 Pandemic in Medan City. The method used in this study is descriptive qualitative through a case study approach to two families who have adolescents with experiences of being exposed to the negative effects of the internet. Data collection was carried out through field observation techniques, interviews and documentation. Informants who were determined as subjects were formulated based on specific criteria and met the requirements in this study. The triangulation technique was carried out to test the validity of the data. The results of this study indicate that consensual family communication patterns have frequent and open communication intensities, while the lasissez-faire family communication intensity is still low so that children tend to be closed. In the process, the two families tend to use a one-way path with situations that are built differently. The communication process between the two families uses aggressive and direct communication techniques. However, on certain topics, consensual families use assertive techniques. The contents of the messages conveyed by parents are about values, morals and religion as a guide for teenagers. The function of family communication as supervision is influenced by education , social and economic level of parents in having digital literacy skills as a guide for teenagers to use the internet wisely.